AJ goes to the dog park [videorecording (Blu-Ray)] - Jones, Toby, 1987-; Thompson, A. J.; Knight, Crystal Cossette; Carlson, Greg; Davy, Danny (Cartuna, 2025)
AJ lives a quiet, ordinary life in the midwest haven of Fargo, North Dakota. His days revolve around small rituals -- morning toast, work as a technical consultant, and cherished afternoons at the local dog park with his two chihuahuas, Diddy and Biff. But when the mayor unexpectedly transforms the park into a sterile blog park with a strict "no dogs allowed" rule, AJ's routine-and sense of peace-is shattered. Determined to reclaim his happy place, AJ embarks on an increasingly surreal odyssey that starts with a goal to unseat the mayor and spirals into a fever dream of animated interludes, amateur brawling, and unexpected cosmic detours. Blending lo-fi live-action with bursts of mixed-media, AJ Goes to the Dog Park is a riotous, offbeat comedy about holding onto the things that matter in a world that won't stop changing. A scrappy, heartfelt debut from Emmy-nominated Toby Jones (Regular Show, OK K.O.! Let's Be Heroes), the film is a love letter to community, canine companionship, and the absurd lengths we'll go to protect what we love.